2015
DOI: 10.1371/journal.pone.0121698
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diabetes, Glycemic Control, and Diabetes-Related Comorbidities on Pulmonary Tuberculosis

Abstract: BackgroundTo assess the influence of diabetes mellitus (DM), glycemic control, and diabetes-related comorbidities on manifestations and outcome of treatment of pulmonary tuberculosis (TB).Methodology/Principal FindingsCulture positive pulmonary TB patients notified to health authorities in three hospitals in Taiwan from 2005–2010 were investigated. Glycemic control was assessed by glycated haemoglobin A1C (HbA1C) and diabetic patients were categorized into 3 groups: HbA1C<7%, HbA1C 7–9%, HbA1C>9%. 1,473 (705 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
94
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 30 publications
8
94
0
4
Order By: Relevance
“…This result is comparable to the result reported in Fiji [31], in Ethiopia [32] and those reported by Kelly Dooley in 2009 [33] but different from the reported study in China [34] in Texas-Mexico [35], Taiwan [36], Maharashtra-India [37], Saudi Arabia [38], and Turkey [39] where sputum conversion among TBDM patient groups were lower. The good sputum conversions observed in both patient groups in our study may be related to good treatment adherence among patients.…”
Section: Discussionsupporting
confidence: 75%
“…This result is comparable to the result reported in Fiji [31], in Ethiopia [32] and those reported by Kelly Dooley in 2009 [33] but different from the reported study in China [34] in Texas-Mexico [35], Taiwan [36], Maharashtra-India [37], Saudi Arabia [38], and Turkey [39] where sputum conversion among TBDM patient groups were lower. The good sputum conversions observed in both patient groups in our study may be related to good treatment adherence among patients.…”
Section: Discussionsupporting
confidence: 75%
“…This delay in DR testing is due to funding limitations, and it is not just a particular situation in Mexico, but for most of the developing countries where TB and T2DM are prevalent. Thus, we find higher number of cases of MDR-TB among TB-T2DM patients, as reported in some studies (Bashar, Alcabes, Rom, & Condos, 2001;Chang et al, 2011;Chiang et al, 2015;Garcia-Garcia et al, 2001), but we cannot distinguish primary from secondary drug resistance cases in TB-T2DM patients. This is a serious limitation that calls for changes.…”
Section: Discussionsupporting
confidence: 69%
“…[11][12][13][14] However, studies in South Korea, Taiwan and Brazil have reported an association of DM with unfavourable outcomes. [7][8][9] These studies also report that unfavourable outcomes were significantly associated with poor glycaemic controls and other comorbidities caused by DM, such as chronic renal diseases, cardiovascular diseases and cerebrovascular diseases in patients with DM. 9 Our results show a higher death rate in patients with DM than in those without DM (20.8% vs. 16.6%).…”
Section: Discussionmentioning
confidence: 98%
“…[7][8][9] These studies also report that unfavourable outcomes were significantly associated with poor glycaemic controls and other comorbidities caused by DM, such as chronic renal diseases, cardiovascular diseases and cerebrovascular diseases in patients with DM. 9 Our results show a higher death rate in patients with DM than in those without DM (20.8% vs. 16.6%). As cause of death is not recorded in the surveillance system, it is unknown whether the high mortality is due to the increased severity of TB in patients with DM or the presence of other factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation